The Huolong cupping therapy combined with complex decongestion therapy and nursing measures in a patient with stage Ⅲ lymphedema of lower limbs complicated with stage Ⅱlymphedema of external genitalia (火龙罐联合综合消肿治疗双下肢Ⅲ期合并外阴部Ⅱ期淋巴水肿1例的护理) - YUAN Huan (袁欢); WU Ting (吴亭); SHI Xiaofei (施小霏); SONG Hongmei (宋红梅) (Association of Integrative Nursing, 2023)
This paper analyzed the intervention effect of Huolong cupping therapy combined with complex decongestion therapy and nursing measures in a patient with stage Ⅲ lymphedema of lower limbs complicated with stage Ⅱ lymphedema of external genitalia after endometrial carcinoma operation. Based on the nursing evaluation, integrative nursing interventions including Huolong cupping therapy by syndrome differentiation, manual lymph drainage, pressure therapy by using low-elastic multi-layer pressure bandage, emotional care, skin care and exercises were carried out to reduce skin fibrosis, promote lymphatic reflux and prevent the infection (本文总结1例龙罐联合综合消肿治疗双下肢Ⅲ期合并外阴部Ⅱ期淋巴水肿1例的护理经验。完善护理评估, 在手法淋巴引流、多层低弹力绷带压力包扎、皮肤护理、运动锻炼等基础上, 基于中医辨证, 采用火龙罐、情志护理等中医护理干预, 促进淋巴液回流, 减轻水肿, 预防感染。)